Silibinin and colorectal cancer chemoprevention: a comprehensive review on mechanisms and efficacy - Raina, Komal (J Biomed Res, 2016)
Globally, the risk of colorectal cancer (CRC) as well as the incidence of mortality associated with CRC is increasing. Thus, it is imperative that we look at alternative approaches involving intake of non-toxic natural dietary/non-dietary agents, for the prevention of CRC. The ultimate goal of this approach is to reduce the incidence of pre-neoplastic adenomatous polyps and prevent their progression to more advanced forms of CRC, and use these natural agents as a safe intervention strategy during the clinical course of this deadly malignancy. Over the years, pre-clinical studies have shown that silibinin (a flavonolignan isolated from the seeds of milk thistle, Silybum marianum) has strong preventive and therapeutic efficacy against various epithelial cancers, including CRC. The focus of the present review is to provide a comprehensive tabular summary, categorically for an easy accessibility and referencing, pertaining to the efficacy and associated mechanisms of silibinin against CRC growth and progression.